2016
DOI: 10.4028/www.scientific.net/kem.696.177
|View full text |Cite
|
Sign up to set email alerts
|

The Balance between Bone Formation and Material Resorption in Unidirectional Porous β-Tricalcium Phosphate Implanted in a Rabbit Tibia

Abstract: We examined the balance between bone formation and material resorption in β-tricalcium phosphate, with unidirectional pores (porosity of 57%) and micropore structure. Using an animal bone defect model, rapid bone formation reached to the center of the material, while the material remained at the same period. Histomorphometric analysis showed that the sum total area of formed bone and material gradually increased with time throughout the experiment. These results indicate that the balance between bone formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 5 publications
0
20
0
Order By: Relevance
“…We observed that new bone formation inside the material is promoted by teriparatide administration in an animal experiment [14]. Since Affinos allows bone marrow blood and platelet-rich plasma to rapidly penetrate material in depth by capillary action, these may contribute to the promotion of new bone formation inside the material [4,13]. Thus, Affinos is expected to become a novel absorbable biomaterial with beneficial features for bone regeneration in orthopedic surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We observed that new bone formation inside the material is promoted by teriparatide administration in an animal experiment [14]. Since Affinos allows bone marrow blood and platelet-rich plasma to rapidly penetrate material in depth by capillary action, these may contribute to the promotion of new bone formation inside the material [4,13]. Thus, Affinos is expected to become a novel absorbable biomaterial with beneficial features for bone regeneration in orthopedic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The porosity of the material is 57% and the initial compressive strength is 8 MPa and 1.5 MPa in directions parallel and perpendicular to the pores, respectively [4]. The most distinctive feature of Affinos is that blood can reach the depths of the material rapidly by capillary action due to its unidirectional porous structure.…”
Section: Figure 1: 3d-ct Image Of Affinosmentioning
confidence: 99%
See 1 more Smart Citation
“…Affinos® (Kuraray Co., Tokyo, Japan), codeveloped with the Department of Orthopedics Surgery, Faculty of Medicine, University of Tsukuba, is a β -tricalcium phosphate ( β -TCP) artificial bone with a porosity of 57% (pore size: 25–300 μ m) and consists of a novel unidirectional porous structure [9]. Using both high-strength and porous hydroxyapatite (HA) and β -TCP would have caused issues with early loading in a pelvic fracture.…”
Section: Introductionmentioning
confidence: 99%
“…Unidirectional porous β-tricalcium phosphate (UDPTCP; Affinos ® , Kuraray Co., Ltd., Tokyo, Japan) is a novel bone-graft substitute, with a porosity of 57%, containing pores with a diameter of 25–300 μm in one direction 1 ) . Animal experiments showed that the the artificial bone with unidirectional pores is characterized by good balance between its resorption and substitution with the autologous bone 2 , 3 ) . However, only a few clinical studies have evaluated its implantation characteristics in humans 4 , 5 , 6 , 7 ) .…”
Section: Introductionmentioning
confidence: 99%